Theory of mechanisms and machines : Lecture notes - Voropay, A. V.; Karpenko, V. A.; Koriak, O. O.; Povaliaiev, S. I.; Sharapata, A. S. (Харківський національний автомобільно-дорожній університет, 2023)
These lecture notes serve as a comprehensive guide to the Theory of Mechanisms and Machines, providing students and professionals in mechanical engineering with a solid foundation in the subject. The content covers key topics such as structure, kinematics, dynamics, force analysis, mechanical transmissions and friction. It delves into the principles governing the design and operation of mechanisms and machines, emphasizing their practical applications in various engineering fields. The lecture notes aim to foster a deep understanding of the fundamental concepts and mathematical methods essential for analyzing and synthesizing mechanical systems. This resource is invaluable for anyone seeking a detailed introduction to the Theory of Mechanisms and Machines, offering insights into the intricate world of mechanical motion and the pivotal role of machines in modern engineering. The presented material allows you to learn the theoretical foundations of mechanics for the possibility of further study of the following special disciplines. The lecture notes is intended for students of technical universities majoring in mechanical engineering.
Теорія механізмів і машин : конспект лекцій
Keywords: kinematics; dynamics; mechanism; force analysis; mechanical transmissions; kinematic chains; efficiency; gear ratio; inertial forces; mechanical components; velocity analysis; acceleration analysis; linkage mechanisms; degrees of freedom; frictional forces; mechanical efficiency; moment of inertia; equilibrium equations; kinematic pairs; power transmission; кінематика; передача потужності; динаміка; механізм; силовий аналіз; механічні передачі; кінематичні ланцюги; ККД; передаточне число; інерційні сили; механічні компоненти; кінематичний аналіз; прискорення; механізми зчеплення; ступені вільності; сили тертя; момент інерції; рівняння рівноваги; механічний ККД; кінематичні пари; сили тертя; момент інерції; рівняння рівноваги; механічний ККД; кінематичні пари; 531.8+621(075)